Early Childhood Development in Tonga : Baseline Results from the Tongan Early Human Capability Index - Brinkman, Sally; Thanh Vu, Binh (World Bank, Washington, DC, 2016)
Early Childhood Development in Tonga offers a comprehensive assessment of early child development across Tonga using the Tongan Early Human Capability Index instrument.